2019
DOI: 10.1371/journal.pone.0215675
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ empathy and attitudes towards professionalism: Relationship with personality, specialty preference and medical programme

Abstract: Background Existing research has suggested that self-reported empathy in medical students is moderated by personality traits and diverse demographic and educational factors including age, gender, nationality, career aspirations, as well as year of curriculum. It is unclear how empathy, personality, and background factors might impact on students’ attitudes towards professionalism in medicine. Methods A cross-sectional questionnaire-based study was conducted in first and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
1
20
0
9
Order By: Relevance
“…The existence of two separate dimensions is in accordance with a previous study conducted in an Irish medical school sample that showed low correlations between empathy and professionalism measures [20]. Montgomery, in a systematic review of the literature to define humanism in the practice of medicine, uses a model centred on the interaction between heart and mind in which the heart represents the emotive domains of empathy, compassion and connectedness while the head represents the cognitive domains of knowledge [21].…”
Section: Plos Onesupporting
confidence: 78%
“…The existence of two separate dimensions is in accordance with a previous study conducted in an Irish medical school sample that showed low correlations between empathy and professionalism measures [20]. Montgomery, in a systematic review of the literature to define humanism in the practice of medicine, uses a model centred on the interaction between heart and mind in which the heart represents the emotive domains of empathy, compassion and connectedness while the head represents the cognitive domains of knowledge [21].…”
Section: Plos Onesupporting
confidence: 78%
“…The influence of individual and environmental factors in the acquisition and development of these three competences has been studied extensively in the last years. Individual factors have been mainly associated with attitudinal abilities ( Hojat and Zuckerman, 2008 ; O’Tuathaigh et al, 2019 ), while the environment has usually been associated with certain academic and clinical settings where professional training of medical students and physicians-in-training is performed ( Hafferty and O’Donnell, 2015 ; San-Martín et al, 2016 ). In fact, a hierarchical environment has been associated with a poor development of teamwork abilities in medicine in comparison with nursing ( Hojat et al, 1997 , 2003 ; San-Martín et al, 2017 ; Tuirán-Gutiérrez et al, 2019 ; Berduzco-Torres et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In three of the 25 competencies (“professional development,” “legal compliance,” and “rapport with patients”), intermediate effects of the standard clinical training were detected, while no effect was detected in another three competencies (“medical equipment management,” “data collection,” and “proper care delivery”). All the three competencies in which intermediate effects were detected are related to personal and professional values that are generally difficult to change [ 34 , 35 ] and could change when systematic education is involved [ 36 , 37 ]. Thus, the standard clinical training program might have successfully enabled new graduate nurses to increase their competencies related to personal and profession values by providing valuable opportunities to cultivate and further change new graduate nurses’ mindsets on nursing professionalism.…”
Section: Discussionmentioning
confidence: 99%